Effect of nurse led education on anxiety level among coronary artery bypass grafting pre-operative patients (Journal of the Pakistan Medical Association, 2020)
Objective: The objective of this study was to identify the effect of nurse-led pre-operative education in minimizing the level of anxiety among patients waiting for Coronary Artery Bypass Grafting. Methods: This experimental study was accomplished at National Institute of Cardiovascular Diseases. Out of 136, there were 80 patients identified with the presence of anxiety using AKUADS 4 to 6 weeks before CABG. Data were collected by the primary researcher from July 2016 to December 2016. Patients with anxiety were divided into experimental and non-experimental groups. After pre-operative education to the experimental group, patients from both groups were re-assessed for anxiety level one week before CABG. Result: Data were assessed through non-parametric Wilcoxon sign ranked and Mann Whitney tests. It was found that anxiety reduced significantly in post-assessment among experimental group participants. No significant difference was found for pre-anxiety assessment between experimental and non-experimental groups. It was noted that post assessment anxiety differed significantly between experimental and non-experimental groups. Conclusion: Pre-operative education was found effective to decrease level of anxiety among patients waiting for CABG. There was no significant difference between pre and post assessment among patients from non-experimental group. Key Words: CABG, Nursing Education, Patients, Anxiety. Continuous...